Woodchip and biochar amendments differentially influence microbial responses, but do not enhance plant recovery in disturbed semiarid soils. (30th April 2020) - Espinosa, Noelle J.; Moore, David J. P.; Rasmussen, Craig; Fehmi, Jeffrey S.; Gallery, Rachel E.
Abstract : Restoration presents a global challenge in drylands (arid and semiarid ecosystems) where uses can range from exclusive conservation to open‐pit mining and restoration practices are constrained by scarce, unpredictable precipitation, and high ambient temperatures. Adding woodchip amendments to soils is a common strategy for mitigating soil degradation as amendments may enhance soil carbon and increase plant cover. We assessed the effect of surface or incorporated woodchip addition and incorporated wood‐derived biochar on soil carbon dynamics and microbial activities as well as plant cover in semiarid soils that had been removed and replaced. We found that woodchips at the soil surface increased soil organic carbon (SOC), and both surface and incorporated woodchips increased the dissolved organic carbon (DOC) content. The incorporation of woodchips inhibited plant cover yet increased soil CO2 efflux and dissolved organic matter stoichiometry. Surface woodchips also significantly enhanced microbial activities but not plant cover. A significant amount of the soil efflux in response to incorporating woodchips was explained by plant cover and exoenzyme activities, but this was not the case for other amendment treatments. Biochar, thought to be more resistant to decomposition, neither stimulated nor reduced microbial activities or plant cover and did not influence SOC or DOC. Our findings demonstrate that the influence of woodchip amendments on microbial processes and soil carbon dynamics depends on the location of application and that coarse fast‐pyrolysis biochar has limited influence on soil processes over a 22‐month study in a water‐limited ecosystem.